Achievement Management of the Patrol Special Operation Division, Metropolitan Police Bureau, Royal Thai Police - Sittiboon, Paitoon; Gerdruang, Asst. Prof. Dr. Atiporn (Journal for Developing the Social and Community, 2019)
The research on the achievement in management of patrol and special operation division, Metropolitan Police Bureau, Royal Thai Police has the objectives of the study as follows: 1) To study the work behavior of the police officers and the achievement in management of patrol and special operation division. 2) To study the influence between the behavior of police officers and the achievement in management affecting the achievement in management of patrol and special operation division. 3) To study the condition of the problems and obstacles, as well as the management guidelines that will help the operation to achieve in management of patrol and special operation division. The researcher used mixed research methods, which conducted the quantitative research before the qualitative research with 306 samples on the quantitative research and 10 samples for the qualitative research. 1.The results indicated that the work behavior of the police officers and the achievement in management of patrol and special operation division in overall has the mean at high level ( = 3.489, S.D. = 0.809) , which included the attitude of work performance aspect ( = 3.598, S.D. = 0.809) , the strength of the work aspect ( = 3.526, S.D. = 0.832) , the international standard operation aspect ( = 3.493, S.D. = 0.826) , and the professional police aspect ( = 3.341, S.D. = 0.726). In addition, it was found that the influence between the work behavior of the police officers and the achievement in management affecting the achievement in management of patrol and special operation division in overall has the mean at high level ( = 3.508, S.D. = 0.789) , which included the organizational culture aspect with the highest mean at high level ( = 3.554, S.D. = 0.744) , the transformational leadership aspect ( = 3.530, S.D. = 0.804) , the organizational characteristics aspect ( = 3.517, S.D. = 0.812) , the good governance aspect ( = 3.505, S.D. = 0.806) , and the administrative resources aspect ( = 3.438, S.D. = 0.825). From the hypothesis testing by multiple regression analysis, it was found that 1) The aspect to create morale and encouragement to the police officers, the aspect of the attitude of work performance, the aspect of the development of operational tools, and the aspect of the development of operational systems influences the overall organizational culture factors. 2) The aspect to create morale and encouragement to the police officers, the aspect of the attitude of work performance, the aspect of the development of police officers’ competencies, and the aspect of the knowledge development for the police officers influence the overall organizational characteristics. 3.The aspect to create morale and encouragement to the police officers, the aspect of attitude of work performance, the aspect of the development of police officers’ competencies, the aspect of the development of operational tools, and the aspect of the development of operational systems influence the overall management resources. The aspect to create morale and encouragement to the police officers, the aspect of the development of police officers’ competencies, the aspect of the development of operational tools, and the aspect of the attitude of work performance influence the transformational leadership aspect in overall. 5) The aspect to create morale and encouragement to the police officers, the aspect of the attitude of work performance, the aspect of the development of police officers’ competencies, and the aspect of the development of operational tools influence the good governance aspect in overall. Therefore, the guidelines for the management are as follows: 1) The organization culture aspect, the management should have the creative vision and develop the operating system to be modernized to the international standards. 2) The organizational characteristic aspect, the command structure should be improved to be able to supervise every subordinate police officers and provide the competency development of the police officers , provide the training course for the officers to be ready to support the situation of the rapidly changing society, and continuously create new knowledge for the police officers. 3) The administrative resources aspect, human resources are important, creating morale and encouragement for the police officers will help them to have a positive perspective on their work performance. 4) The transformational leadership aspect, the leaders should have the positive attitude in performance, dare to make clear decisions. And 5) The good governance aspect, the organization executives should have the moral courage, as well as develop the operational tools to complete the mission, according to the goals for the benefit of the people and peaceful nation based on the legitimacy.